Living longer but in poor health: healthcare system responses to ageing populations in industrialised countries based on the Findings from the Global Burden of Disease Study 2019 - Minjae Choi; Joshua Kirabo Sempungu; Eun Hae Lee; Yo Han Lee (BMC, 2024)
Abstract Objectives This study aimed to examine changes in life expectancy (LE), health-adjusted life expectancy (HALE), unhealthy years of life, and disease burden of older people in industrialised countries and associations with health systems. Methods We used estimates of LE and HALE, unhealthy years of life, years of life loss (YLL), years lived with disability (YLD) for individuals aged 70 years and over in 33 industrialised countries from 1990 to 2019 from the Global Burden of Disease Study 2019. A linear regression analysis was conducted to examine the association of health outcomes with the Healthcare Access and Quality (HAQ) index. Results LE and HALE increased with improved HAQ index from 1990 to 2019. However, the number of unhealthy years of life increased. An increased HAQ index was associated with decreases in YLL. However, changes in YLD were relatively small and were not correlated with HAQ index. Conclusions The healthcare system needs to more address the increased morbidity burden among older people. It should be designed to handle to healthcare needs of the ageing population.